In Vitro Incidence of Fibular Penetration With and Without the Use of a Jig During Tibial Plateau Leveling Osteotomy. Issue 4 (11th March 2014) - Flynn, Patrick; Duncan, Colleen G.; Palmer, Ross H.; Duerr, Felix M.
<x xml:space="preserve">Abstract</x> Objective To determine the incidence of fibular penetration during placement of the Synthes® locking TPLO plate with and without the use of a jig. Study Design Cadaveric, experimental study. Sample Population Cadaveric paired pelvic limbs (n = 8) from skeletally mature dogs. Methods Limbs were assigned to 1 of 2 groups (jig‐less‐TPLO = no jig used; jig‐TPLO = jig used). Synthes® locking TPLO plates were applied using proximal screws of excessive length to facilitate identification of fibular penetration. Screw tip locations were identified by dissection and frequency of fibular penetration was compared between groups. Results None of the jig‐TPLO limbs and 6 (75%) of jig‐less‐TPLO limbs had fibular penetration, a difference that was statistically significant. Fibular penetration was most frequently associated with the most proximal screw. Conclusions A significantly higher incidence of fibular penetration occurs when Synthes® locking TPLO is performed without use of a jig.